Oral vancomycin induces sustained deep remission in adult patients with ulcerative colitis and primary sclerosing cholangitis. Issue 10 (October 2018) - de Chambrun, Guillaume Pineton; Nachury, Maria; Funakoshi, Natalie; Gerard, Romain; Bismuth, Michael; Valats, Jean-Christophe; Panaro, Fabrizio; Navarro, Francis; Desreumaux, Pierre; Pariente, Benjamin; Blanc, Pierre
Abstract : Ulcerative colitis (UC) is a chronic inflammatory bowel disease of unknown etiology. The treatment of UC is challenging, especially when it is associated with primary sclerosing cholangitis (PSC), a chronic inflammatory disease of the bile ducts that affects around 5% of patients with UC, and leads to an increased risk of cholangiocarcinoma and colorectal cancer. Microbiota is considered to play an important role in the pathogenesis of UC, although the efficacy of antibiotics in this context is only limited and transient. Several studies have investigated the use of antibiotics for the treatment of PSC in adult and pediatric populations, with conflicting results. In this brief report, we describe the effect of oral vancomycin treatment in three patients with UC and PSC refractory to conventional and biologic therapies. All three patients achieved clinical remission and mucosal healing with vancomycin 500 mg twice a day administered orally. Maintenance treatment with oral vancomycin was well tolerated and led to sustained clinical and endoscopic remission in all three patients. Oral vancomycin also improved liver function tests in two patients who did not have pre-existing cirrhosis. Abstract : Supplemental Digital Content is available in the text.